Selecting a Method of Case Identification to Estimate the Involvement of People With Mental Illnesses in the Criminal Justice System: A Research Note. (June 2017) - Morabito, Melissa S.; Wilson, Amy Blank
Arrest and incarceration are a pervasive reality for people with mental illnesses. Wide variation, however, exists in the estimates of the percentage of people with mental illnesses who become involved in the criminal justice system. Researchers and practitioners need a variety of methods in their toolbox to maximize their ability to identify mental illness depending on available resources and needs. Yet, the benefits and costs of utilizing these different approaches have yet to be explored in the criminal justice literature. To begin exploring the utility of the different methods of case identification, we review the most commonly used approaches to identifying people with mental illnesses and end with a detailed examination of the use of behavior health records. The use of behavioral health records is a case identification method that has gained emerging support in criminal justice research in recent years.